2018
DOI: 10.12956/tjpd.2018.398
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Peer Bullying with Cyberbullying and Anger Expression Styles in Adolescents Attending a Child Psychiatry Clinic

Abstract: ÖZAmaç: Ergenler arasında akran zorbalığı evrensel bir sorundur. Çalışmada klinik örneklemde ergenlerde akran zorbalığının demografik değişkenler, siber zorbalık, siber mağduriyet ve öfke ifade tarzlarıyla ilişkisinin incelenmesi amaçlanmıştır. Gereç ve Yöntemler:Çocuk psikiyatri polikliniğine başvuran 61 ergen çalışmaya alındı. Sosyodemografik form, Sürekli Öfke ve Öfke Tarz Ölçeği, Akran Zorbalığı Belirleme Ölçeği-Ergen Formu, Siber Zorbalık Ölçeği ve Siber Mağduriyet Ölçekleri kullanıldı. Ergenlerde psikopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Thus it appears as refugee adolescents are exposed to bullying, their likelihood of exhibiting bullying behavior also increases. Çelen et al (2020) reported that 78.7% of the adolescents in their study were in the bully/victim cycle. Similarly, Lereya et al (2015) stated that both children who are bullied and those who bully to protect themselves are in a risky situation in terms of psychological health.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus it appears as refugee adolescents are exposed to bullying, their likelihood of exhibiting bullying behavior also increases. Çelen et al (2020) reported that 78.7% of the adolescents in their study were in the bully/victim cycle. Similarly, Lereya et al (2015) stated that both children who are bullied and those who bully to protect themselves are in a risky situation in terms of psychological health.…”
Section: Discussionmentioning
confidence: 89%
“…Those who are bullied can also bully as a coping strategy. Çelen et al (2020) found that 78.7% of adolescents are both bullies and victims. Similarly, Gökkaya and Tekinsav‐Sütcü (2020) reported that boys are more bully‐victims than girls.…”
Section: Introductionmentioning
confidence: 99%